Posterior Reversible Encephalopathy Syndrome with Stroke in Puerperal Woman with High Titer of Anti-Phospholipid IgM Antibody - Hiroto Hirashima; Masahiro Iwamoto; Tadashi Ozawa; Shigeyoshi Kijima; Shigeki Matsubara; Akihide Ohkuchi (Case Reports in Obstetrics and Gynecology)
Posterior reversible encephalopathy syndrome with stroke is very rare in puerperal women. A 36-year-old nulliparous woman with both rheumatoid arthritis and recurrent pregnancy loss, probably due to a high titer of anti-phospholipid IgM antibody, was referred at 10 weeks of gestation. Low-dose aspirin at 100 mg/day and heparin calcium subcutaneous injection at 10,000 units/day were started before pregnancy and stopped at 35+6 and 40+2 weeks, respectively. She transabdominally delivered a male infant weighing 3,344 g at 40+5 weeks. A tonic-clonic seizure abruptly occurred without either hypertension or proteinuria 5 days after delivery. Intracerebral hemorrhage involving an area of 2 cm in diameter in the right frontal lobe and subarachnoid hemorrhage with PRES were confirmed. Seizure recurred 2 days after the initial episode. She showed severe headache and mild disturbance of consciousness but no neurological findings. We suggested that a high titer of anti-phospholipid IgM antibody might be associated with stroke.